2014
DOI: 10.1159/000365925
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Infective Dose of H9N2 Avian Influenza Virus in Different Routes: Aerosol, Intranasal, and Gastrointestinal

Abstract: Background: Low pathogenic H9N2 avian influenza virus (AIV) has been spreading worldwide, leading to huge economic losses to poultry husbandry, but few studies were concerned about its aerosol infection. Methods: This study compared the infective doses of H9N2 AIV to chickens by three different routes, aerosol infection, intranasal and gastrointestinal infection, and determination of the results was conducted by detecting virus shedding and seroconversion of chickens. Results: The results indicated that chicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Swayne and Beck (2005) reported that specific pathogen-free (SPF) chickens fed with breast and thigh meat (harvested from chickens 3 days post-inoculation with H7N2 LPAIV) did not show any clinical signs, neither produced antibodies to the virus nor died. These results are in line with the study of Swayne and Beck (2005), who described infection of chickens fed with HPAIV only when a dose was available above the median infection dose determined by Yao et al (2014). This is the only study that could be identified where (starved) poultry were exposed to meat from LPAI-inoculated birds.…”
Section: Commercial and Non-commercial Poultrysupporting
confidence: 88%
See 1 more Smart Citation
“…Swayne and Beck (2005) reported that specific pathogen-free (SPF) chickens fed with breast and thigh meat (harvested from chickens 3 days post-inoculation with H7N2 LPAIV) did not show any clinical signs, neither produced antibodies to the virus nor died. These results are in line with the study of Swayne and Beck (2005), who described infection of chickens fed with HPAIV only when a dose was available above the median infection dose determined by Yao et al (2014). This is the only study that could be identified where (starved) poultry were exposed to meat from LPAI-inoculated birds.…”
Section: Commercial and Non-commercial Poultrysupporting
confidence: 88%
“…In another experiment, it was demonstrated that infection of chickens through oral exposure of chickens to meat containing HPAI H5N1 (isolate A/whooper swan/Mongolia/ 224/05) required a dose 3-4 log 10 times higher than through intranasal exposure (Kwon et al, 2010). Yao et al (2014) assessed the dose-response relationship of chickens challenged intranasally and gastrointestinally with H9N2 LPAIV. This result is in line with the absence of virus in muscle tissue of the originally inoculated chickens.…”
Section: Commercial and Non-commercial Poultrymentioning
confidence: 99%
“…Many studies have implicated direct contact as an important transmission route for H9N2 viruses in chickens, although indirect routes such as aerosol and faecal-oral have been shown to be important for some strains and many viruses show primarily a respiratory tropism. Although some H9N2 strains have been shown to have an extended tropism in the kidneys or oviducts [80][81][82][83][84][85]. Both of 32…”
Section: H9n2 Virus Transmission and Host Tropism In Poultrymentioning
confidence: 99%
“…in the field and experimentally poultry adapted H9N2 viruses are mostly detected from buccal rather than cloacal swabs [15,67,86]. Additionally inoculation of some H9N2 viruses into the respiratory tract is 40 times more effective than gastrointestinal inoculation at initiating infection [84]. However, many of these routes appear to be environmentally contextual, for example, at LBMs communal water sources have been implicated as the major route of transmission of endemic H5N1 and H9N2…”
Section: H9n2 Virus Transmission and Host Tropism In Poultrymentioning
confidence: 99%
“…In influenza research, intranasal instillation is an extensively applicable method to infect mammals, including mice, ferrets, and pigs, but does not reflect the natural infection route in humans; for example, nonhomogeneous distribution of the virus in the lungs can affect early intrapulmonary distribution, as well as viral retention and clearance kinetics, and does not reflect the natural H1N1 infection course in humans . The route of virus inoculation in mice and the anesthesia used during administration can greatly influence clinical symptoms and experimental data postinfection . Here, the aerosol inhalation route, which resembles the natural infection route, was selected to challenge BALB/C mice with H1N1 aerosol, and we identified significant differences in disease progression, lung pathology, and peak virus replication in BALB/C mice infected with influenza A (H1N1) virus via the aerosol and instillation routes.…”
Section: Discussionmentioning
confidence: 99%